Urgensi Fiqih Nadzar Dalam Proses Pernikahan - Dodi Yarli R (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
The least knowledge of fiqh in Islam resulted in many people who violate it. such as marriage issues. many people do not know about fiqh in the marriage process. So many who do wrong before marriage with courtship or free sex that is prohibited in Islamic law is prohibited.in Islamic law one of the processes in marriage is to see (nadzar) the prospective wife or husband. Seeing a potential wife or husband to be one cause to achieve happiness in the family. Prophet Muhammad advised his followers to see his future wife, so do not regret after married.